Pertimbangan Hukum Pergantian Kelamin - Jacqueline Leticia Latifa (Departement of Mathematics Education, 2023)
Along with the development of technology and the times, many people carrying out sex reassignment which causing pro and contra because there is no law regulates sex reassignment. Based on Article 10 paragraph (1) of Law Number 48 Year 2009 concerning Judicial Power, the judge may not reject the case that goes to court. The method used in this study is normative juridical, which is an approach that is carried out by examining existing library materials. The judges of the Yogyakarta District Court in granting the request for sex reassignment only considered positive law, while the Boyolali District Court judge in granting the request for sex reassignment not only considered positive law but also used Islamic law and MUI fatwas. In the context of maslahah, both the Yogyakarta District Court judges and the Boyolali District Court judges, both considered the problems or benefits for the applicant sex reassignment. Requests for gender reassignment in court are filed after sex reassignment has been carried out so that the function of the court is only as a formal legality of the practice of sex reassignment.